The innovative breakthrough of neurocounseling through overview of phobia student’s brain waves - Azmi, Khilman Rofi (Universitas Negeri Padang, 2019)
Counselors are striving to make sure that their counseling process is scientifically based. A new Counseling paradigm that related to neuroscience, called Neurocounseling, is acknowledged by the American Counseling Association (ACA) and became a new branch of Counseling in 2015. This study is used Neurocounseling paradigm to understanding the psychological condition of the client (student) in the counseling stage. Preliminary study showed us that 46 students from 80 students had showed phobia symptom. It means that 50% students are suffering learning disorder with various levels. We designed our research to record students with phobia symptom’s brainwaves through Electroencephalography (EEG). The record of counselee brainwave will make counselors achieve a better result of counseling because it will help them to choose the right counseling technique. We used qualitative approach and case study to find out student with phobia symptom’s brainwave and mental condition. We used some data collecting techniques: interview, observation, and documentation. The finding showed us that the main brain wave of counselee with phobia symptom is Beta wave in frequency 20-30Hz, it means counselee has a high level of anxiety. Counselee also had a deep tension on nerves and muscles during brainwaves record in the counseling process.